Kajian Sifat Fisik Tanah Ustifluvents Sekotong Terkait Kandungan Merkuri (Hg) Dalam Tanah: Assesment of Physical Properties of Ustifluvents Sekotong Releted to Mercury (Hg) Content in Soil - Puji Hapsari Hurum; Zaenal Arifin; Padusung Padusung; Suwardji Suwardji (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
People's gold mining in Sekotong, also known as Unlicensed Gold Mining (PETI), causes environmental pollution problems because located at the surrounding community processes gold using the amlagamation technique with the help of mercury (Hg) in binding gold. Mercury waste discharged directly into the environment could have adversely affects public health and degrades soil and water quality. The presence of mercury in the soil is strongly influenced by soil characteristics, one of which is soil physical properties. The purpose of this study was to determine the relationship between the physical characteristic ustifluvents Entisol soil of Sekotong soil and mercury content at 0-20 cm soil depth. This research was conducted using descriptive method with survey technique. Soil sampling was conducted at 3 location points near the logs and tailling at a depth of 0 - 10 cm and 10-20 cm, each location point was replicated 3 times. The selection of soil sample points was based on contour differences that affect the proportion of mercury content at each soil depth. The results showed that the highest mercury content was at point 3 with an average value of 0.3089 ppm and there was a strong to very strong relationship between soil physical properties and Hg content.